Двофононне наближення у задачах перенормування енергетичного спектра квазічастинки у плоскій напівпровідниковій наноплівці - Крамар, В.; Ткач, М.; Курганецький, М. (Праці наукового товариства ім. Шевченка, 2011)
The effect of electron-phonon interaction on the bottom of ground energy band of an electron in the flat nanofilm with finite quantum well was studied by Green s function method. The analytic expression was obtained for the mass operator that takes into account the two-phonon processes of electron interaction with confined phonons in the case of T = 0 K. Taking as an example different materials with different values of a coupling constant it is shown that the two-phonon processes being taken into account make it possible to more carefully determine the magnitude of electron s energy in comparison with the results of one-phonon approach. Percentage error of these two con sequent approaches in the studied nanostructures reaches 1.5 - 14.4% and increases by linear law when the coupling constant increases.